SOIL CO2 EMISSION ASSOCIATED WITH LIMING IN AREA OF CONVERSION OF ORANGE FOR SUGAR CANE - Silva, Eliton de F. [UNESP]; Moitinho, Mara R. [UNESP]; Teixeira, Daniel de B. [UNESP]; Pereira, Gener T. [UNESP]; La Scala Junior, Newton [UNESP] (Soc Brasil Engenharia Agricola, 2014)
The soil CO2 emission (FO2) in agricultural areas is resulting from the interaction of several factors, as amended by the practice of soil management practices and crop, in addition to the local edaphoclimatic conditions. In this study, we aimed to quantify FO2 influenced by liming and application position (row and interrow old) of the orange crop in conversion area for cultivation of sugar cane in the municipality of Frutal-MG. The treatments evaluated were: Row/CC (row with lime application), Interrow/CC (interrow with application of lime), Row/SC (row without liming) and Interrow/SC (interrow without liming). FCO2, temperature (Ts) and soil moisture (Us) were evaluated over 12 days. The highest average value of FCO2 over the study period was observed in the treatment Row/CC (9.63 mu mol m(-2) s(-1)) and the lowest in Interrow/CC (5.92 mu mol m(-2) s(-1)) according to the Tukey test. The FCO2 was negatively correlated with Us in Row/CC (r = -0.56, p < 0.05) and in Row/SC (r = -0.66, p < 0.05). It was also observed a significant and positive correlation between FCO2 and Ts in Row/CC (r = 0.76, p < 0.001), Row/SC (r = 0.89, p < 0.001) and in Interrow/SC (r = 0.66, p < 0.05). It was observed that liming and position of application (row and interrow) influenced the soil CO2 emissions.
Keywords: liming; soil respiration; soil temperature; soil moisture